The use of the SIMDA application in accounting department at regional hospital Siti Fatimah Palembang - Ayu Chairina Laksmi; Aradiva Mardhatila (Proceeding International Conference on Accounting and Finance, 2023)
This paper aims to show how effective and the obstacles faced when using the SIMDA application in the Accounting Section of Siti Fatimah Hospital Palembang in producing financial reports. There are several previous studies that have examined the use of the SIMDA application in the preparation of financial reports in several types of institutions, but there has been no research that discusses the use of the SIMDA application in hospital institutions. In terms of expanding the previous study, this research method uses internal hospital data related to inputting financial transaction data on the SIMDA application. Finally, this study found that the use of the SIMDA application in producing financial reports was more effective than entering financial transaction data manually from one book to another. In this study found obstacles and shortcomings in using this application at the Hospital Accounting Department.